The Civilization of the Criminal Law - Slobogin, Christopher (2005)
The boundaries of the criminal justice system are eroding. A vast amount of relatively innocuous behavior is now criminalized. The line between criminal penalties and administrative sanctions is dissolving, as criminal law relaxes its mens rea requirements and government bureaucracies aggressively pursue regulatory violations. Distinctions between criminal and civil forfeiture, contempt, and deportation proceedings have been vanishingly subtle for some time. Perhaps the most serious assault on the integrity of today's criminal justice system, however, is the increasing prominence of the dangerousness criterion as justification for confinement by the government. Governmental deprivations of liberty have usually been the province of the criminal law, which is generally defined by a commitment to punishing individuals for their past acts based on the principle of just deserts. Constraints on liberty based upon dangerousness, in contrast, focus on the individual's future actions. These latter types of interventions contemplate neither punishment nor an assessment of blameworthiness for previous conduct, and thus directly flout the traditional premises of criminal justice. This Article contends, contrary to the views of most legal commentators, that this development ought to be encouraged. The criminal law ought to embrace the dangerousness criterion, with the significant caveat that it do so wholeheartedly rather than in the halting manner it has exhibited to date. The punishment model of criminal justice that views desert, general deterrence, or inculcation of good character (or some combination of these three) as the primary objective of criminal justice should be discarded, and individual prevention should become the predominant goal of the criminal justice system